CONCEPTUALISATION OF QUALITY OF LIFE IN NURSING - Gurková, Elena; Žiaková, Katarína (Profese Online, 2009)
Authors analysed the concept quality of life through three approaches: psychological, application and integrating approach. They focused on the conceptual difference between concepts quality of life, well-being and satisfaction in the psychological approach. They also analysed differencies between concepts health, health status and quality of life in evaluation of the application approach. In the third approach they integrated components and determinats of quality of life into specific theoretical framework. They used a method of conceptual analysis to determine defining characteristics of quality of life in nursing.
Keywords: quality of life; health; well-being; satisfaction; conceptual models